Prosedur Mekanisme Pengembalian Aset Negara Hasil Tindak Pidana Korupsi di Indonesia - Koy, Yunita Inoriti (Politeknik Amamapare, 2024)
Corruption is a nista act that takes place every year. Corruption is classified as a heinous act and has a major impact on state finances to the detriment of many parties. Investigation, prosecution, and examination in court hearings in cases of corruption must take precedence over other cases for immediate resolution. The purpose of this study is to understand and analyze law enforcement of corruption in Indonesia and to understand and analyze the mechanism of returning state assets resulting from corruption crimes. The method used in this study is a normative research method, namely legal research that puts the law as a building of a norm system. Law Number 20 of 2001 concerning Corruption regulates mechanisms or procedures that can be used to return assets through criminal and civil channels. The mechanism for returning state assets resulting from corruption can be carried out with two mechanisms at once, namely through criminal channels (criminal) as stipulated in UNCAC and civil forfeiture. The criminal path is intended to provide a deterrent effect to the corruptors so that the corruptors do not repeat the criminal act of corruption. The civil forfeiture is intended to return state assets resulting from corruption crimes with evidence obtained from criminal proceedings, namely asset tracing and freezing. The key to success lies with each country, so it cannot be determined which mechanism is best. The element of success in making efforts to return assets resulting from corruption must pay attention to several factors, one of which is the perspective on the law enforcement approach in Indonesia still focuses on prosecuting perpetrators (in personam), not seizing assets resulting from crime.